The effect of MDMA and pentoxifylline drug on bad/bcl-xl gene dosage expression changes on rat liver - Behroozaghdam, Mitra; Hashemi, Mehrdad; Javadi, Gholamreza; Mahdian, Reza; Soleimani, Mansoureh; Nadia Sharifi, Zahra; Movaseghi, Shabnam (Archives of Advances in Biosciences, 2015)
MDMA generally known as ecstasy, have deleterious effects on the serotonergic neurotransmitter system. Recent findings suggest that the liver and brain are major target organs of MDMA-related toxicities. Although most research is being dynamically performed on brain, however, the molecular mechanisms by which MDMA elicits adverse effects in both organs are poorly undrestood.The present study was performed to obtain evidence for molecular mechanism of apoptosis involved in MDMA-induced hepatotoxicity in rat liver after MDMAadministration. Moreover, the antagonistic effect of pentoxifylline was assessed on hepatotoxicity after MDMA administration. In this experimental study, sample size and power in each group were calculated as 10 rats with 95% confidence level and 5% confidence interval. In the study, four experimental groups were selected including Control Normal, MDMA, MDMA+PTX and PTX+MDMA. MDMA was dissolved in PBS and intraperitoneally injected three doses of 7.5mg/kg with two hours gap between doses. Pentoxyfilline also was injected as 100mg/kg, simultaneously with third dose of MDMA. After treatment, total RNA was isolated from liver tissue (5mg). Absorbance at 260nm, 280nm and 230nm were measured and immediately reverse transcription was performed. Included target genes were BAD and BCL-XL as pro-apoptotic and anti-apoptotic gene, respectively. After set up and validation, Real-Time PCR were performed and obtaining data were statistically analyzed to determine significantly differences between groups. Using Real-Time quantitative PCR results, BCL-XL gene expression ratio significantly increased in MDMA+PTX group. Moreover, BAD gene expression ratio increased and up-regulated in PTX+MDMA group (P-value <0.001).Our study focused on molecular mechanism of MDMA in programmed cell death using gene expression quantification of a pro-apoptotic and anti-apoptoic gene in MDMA-induced hepatotoxocity. The results shown MDMA prompted apoptosis in liver and pentoxifylline protects hepatotoxicity after and befor taking MDMA.